Reformation of Islamic Family Law in Indonesia : The Nusyuz Resolvation Process - Rizqa Febry Ayu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
Family law has an important position in Islam. Updates were made to respond to the usual conditions. As an ireform religion, Islam changes the order of life. The family system is an issue that is being updated. Two important points were discussed, namely the concept of Islamix law and the renewal of Islamic family law in Indonesia towards the nusyuz settlement process. The purpose of this study is to find out how to reform Islamic family law in Indonesia and the concept of nusyuz that fits the current situation. The research method used is a literature review, collecting data from the literature so that t is related to the theme under study, and collecting data using descriptive qualitative techniques. The modernity of nusyuz, according to the author, for the current context, it is clear that women should not be treated like women during the jahiliyyah period. That today’s women can be seen not only play a role in the domestic sphere (housewives), but also have a role in the public sphere starting from educational needs, even professional demans that require wives to enter and leave the house freely. So the meaning of nusyuz at the present time must be understood more deeply whether the wife or even the husband has actually committed real disobedience, because the conditions of the present must be different from the past.Hukum keluarga mempunyai posisi yang penting dalam Islam. iPembaruan idilakukan iuntuk imenjawab ikondisi izaman. iSebagai iagama ipembaruan, iIslam imengubah itatanan ikehidupan. iSistem ikekeluargaan iadalah isalah isatu ihal iyang idiperbarui. Dua poin penting yang dibahas yaitu konsep hukum Islam dan pembaruan hukum keluarga Islam di Indonesia terhadap proses penyelesaian nusyuz. Tujuan penelitian ini untuk mengetahui bagaimana pembaruan hukum keluarga Islam di Indonesia serta konsep nusyuz yang cocok dengan keadaan sekarang. Metode penelitian yang digunakan adalah kajian pustaka, mengumpulkan data-data yang bersumber dari literatur sehingga berkaitan dengan tema yang diteliti, dan pengumpulan data menggunakan teknik kualitatif deksriptif. Modernitas nusyuz menurut penulis untuk konteks saat ini jelas bahwa perempuan seharusnya tidak diperlakukan layaknya perempuan pada masa jahiliyyah. Bahwa perempuan masa kini dapat dilihat tidak hanya berperan dalam ranah domestik (ibu rumah tangga) saja, namun juga memiliki peran dalam ruang publik mulai dari kebutuhan pendidikan, bahkan tuntutan profesi yang mengharuskan istri keluar masuk rumah secara bebas. Maka pemaknaan nusyuz pada masa sekarang harus dipahami lebih mendalam apakah istri atau bahkan suami benar-benar telah melakukan pembangkangan yang nyata, sebab kondisi masa kini pasti berbeda dengan masa lalu.